Evaluation of Premature Ventricular Contractions in Children with Structurally Normal Hearts: A Single-Center Study - Merve Tosyalı; Ertürk Levent (Galenos Yayinevi, 2024)
Aim: Premature ventricular contractions are a prevalent arrhythmia in children, with the majority of cases exhibiting normal cardiac function and no anatomical abnormalities. The objective of this study was to assess the clinical course of premature ventricular contractions in children who do not have any structural heart abnormalities. Materials and Methods: In this study, 60 patients younger than 18 years of age who were diagnosed with premature ventricular contractions in our clinic and who did not have any structural cardiac abnormalities on echocardiography were included. Demographic data, 12-channel standard resting electrocardiography, 24-hour Holter electrocardiography monitoring, and the exercise test records of the patients were retrospectively analyzed from their follow-up files. Results: This study assessed 60 patients diagnosed with premature ventricular contraction, of whom 55% were male. Out of the total number of patients, 28 (46.7%) were asymptomatic, while the most often reported symptom was palpitations. Additionally, it was stated that five children had syncope. Medical treatment was given to 40 patients (66.7%). Beta-blockers (52.2%) were the most commonly prescribed drugs. Malignant arrhythmia or sudden cardiac death did not occur in any of the patients throughout the follow-up period. According to all patients' follow-up Holter electrocardiography results, a 61.6% decrease in premature ventricular contraction rates was observed. Complete recovery was observed in 16.7% of the patients. Conclusion: Premature ventricular contractions in children generally have a good prognosis. Most cases are asymptomatic, and regardless of the origin, spontaneous regression rates over time are quite substantial. Determining the origin may help predict the prognosis.